Rancangan Monitoring Wind Direction Indicator Berbasis Arduino di Bandar Udara Indonesia - Rossydi, Ahmad; Yuyun Irmayanti, Andi; Sugiyanto (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2021)
Windsock is a marker of wind and relative wind speed. This tool is very useful in the world of aviation. Every airport must have a windsock as a support for determining the direction of the wind. This tool is installed at an airport that can be seen clearly by air traffic officers (ATC). But at the airport, A.P.T. Pranoto-Samarinda still uses a manual system to view the windsock using long-distance binoculars. The background of the development of this tool is due to the lack of effectiveness and efficiency when using the windsock which is already available at A.P.T Airport. Pranoto Samarinda. So here the author is interested in raising a title in this final project, namely "Designing of Arduino-Based Wind Direction Indicator Monitoring at Aji Pangeran Tumenggung Airport, Pranoto-Samarinda". The final result achieved from the development of this windsock is that the aim is not to find the wind direction manually, with the development of this tool it can find the wind direction automatically. This windsock is also equipped with a wind vane and a winding cone to measure the wind direction and wind speed around the device. The design of the Arduino-based Wind Direction Indicator monitoring system is expected to detect wind speed and direction that is able to provide data in real-time. So that the data obtained can be conveyed to the public quickly and accurately, an adequate system is needed. The system that is currently growing rapidly is Personal Computer (PC) and internet network. The design of this Wind Direction Indicator tool consists of hardware in the form of Arduino, direction sensor, and wind speed sensor. The Wind Direction Indicator tool can help facilitate ATC in monitoring wind direction and speed which is very important for flight, where previously this process used binoculars to monitor wind direction. The process of monitoring wind direction is made easier by using this tool because the results of reading wind direction and speed will immediately appear on the monitor.